Generalklausul mot skatteflykt - Rosander, Ulrika (Internationella Handelshögskolan, 2007)
Skatteflykt motverkas i många rättssystem genom åtgärder på olika nivåer. I Sverige är en av de metoder som används en lagstiftad generalklausul mot skatteflykt, skatteflyktslagen. Såväl rättssäkerhet som skattesystemets effektivitet anses vara grundläggande värden att upprätthålla i det svenska skattesystemet. Skatteflyktsproblematiken innebär dock att dessa båda värden i vissa situationer inte samtidigt kan uppfyllas fullt ut, vilket innebär att ett rättsligt område skapas där det blir nödvändigt att göra kompromisser och avvägningar. Det är den här balansen som är den stora utmaningen gällande åtgärder mot skatteflykt och som blir mycket tydlig gällande skatteflyktslagen. Avhandlingen analyserar generalklausuler mot skatteflykt ur ett rättssäkerhets- och effektivitetsperspektiv. Denna analys genomförs i form av en komparativ studie av Sveriges, Kanadas och Tysklands generalklausuler mot skatteflykt. Användandet av en generalklausul jämförs också med användandet av en praxismetod, vilket är den andra repressiva metoden mot skatteflykt som är frekvent förekommande i olika rättssystem världen över. Det konstateras att det är många olika frågor vid sidan av den konkreta rekvisitkonstruktionen och tillämpningsområdet som påverkar vilken rättssäkerhet och effektivitet som en generalklausul mot skatteflykt uppnår. Hur domstolssystemet ser ut, vilken inställning som finns till lagtolkning och hur domstolarna och skattemyndigheten väljer att tillämpa klausulen är exempel på mer generella frågor som har stor betydelse. Men även t.ex. relationen till andra metoder mot skatteflykt, möjligheten att erhålla förhandsbesked och vilka administrativa specialregler som används påverkar. I avhandlingen framför författaren sin uppfattning om vilka områden som är av störst vikt att utveckla i svensk rätt för att stärka skatteflyktslagens rättssäkerhet och effektivitet i framtiden.
Keywords: Fraude fiscale; Skatterätt; Tax fraud; Tax law

Quinze ans de restructuration bancaire dans la CEMAC : qu’avons-nous appris ? - Avo, Désiré; Eyeffa Ekomo, Sylvie Marie-Louise (Revue d'économie financière, 2007)
Les pays de la Communauté économique et monétaire de l’Afrique centrale (CEMAC) ont connu, à partir du début des années 1980, une grave crise économique. Les conséquences de celle-ci se sont traduites, sur le secteur bancaire, par une dégradation rapide et brutale du portefeuille des banques. En réponse à cette crise, les autorités monétaires, avec l’appui de la communauté financière internationale ont engagé une politique de restructuration bancaire. Cette politique avait pour objectif d’assurer un retour à la stabilité bancaire en améliorant les circuits de financement. L’objectif de cet article est de montrer, après avoir présenté les différentes réformes qui ont été mises en oeuvre, que les restructurations bancaires, au lieu d’assurer le financement de l’économie, ont plutôt conduit à des paradoxes dont trois sont particulièrement développés. Il s’agit de : la surliquidité et le rationnement du crédit ; la concentration bancaire et le développement de la microfinance et enfin l’internationalisation bancaire sans développement des innovations financières. Fifteen years of banking restructuring in CEMAC : what have we learnt ? Member countries of the Central African Economic and Monetary Community (CEMAC) experienced a severe economic crisis since the 80’ s. As a consequence of this prolonged crisis, the portfolio of commercial banks dramatically deteriorated, therefore pushing monetary authorities and international community to envisage a restructuring strategy for the banking sector. The aim of this strategy was to stabilize the banking sector by improving financing channels and mechanisms. In this paper we show that the reforms implemented to restructure the banking sector, far from having improved financing mechanisms, have led to the emergence of three paradoxes : excessive liquidity of the system coupled with credit rationing, banking concentration and contemporaneous development of microfinance structures and foreign penetration in the banking sector without development of financial innovations.

Accounting for financial instruments: An analysis of the determinants of disclosure in the Portuguese stock exchange - Lopes, Patrícia Teixeira; Rodrigues, Lúcia Lima (The International Journal of Accounting, 2007)
In this paper we analyse the determinants of disclosure level in the accounting for financial instruments of Portuguese listed companies. Considering the mandatory adoption of International Accounting Standards after 2005, our ultimate objective is to analyse the characteristics of companies that are closest to the disclosure requirements of IAS 32 and IAS 39. We have constructed an index of disclosure comprising 54 items based on IAS 32 and 39 disclosure requirements and computed the index score for each Portuguese listed company based on the analysis of the companies’ annual reports. We tested the relation between the index score and several firm-specific characteristics: size, industry, auditor type, listing status, multinationality degree, relationship shareholders/creditors and importance of shareholders. We conclude that larger companies and companies listed in more than one exchange market show higher levels of disclosure, meaning that they are closer to IAS 32 and 39 requirements. We argue that the agency theory, the signalling theory and the political costs theory do not fully explain Portuguese reality, where there is a large degree of family ownership and bank-oriented financing policies. We therefore advocate that the introducing variables related to specific characteristics of Portuguese companies and managers, in the context of other theoretical frameworks, notably the contingency theory, brings important insights to this type of analysis.